Use of Hydrogen Peroxide (H2O2) in raw cow’s milk preservation (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: Hydrogen peroxide (H2O2) was used for the activation of lactoperoxidase system on preservation of milk.Materials and methods: Milk samples were collected from Bangladesh Agricultural University dairy farm. The collected milk samples were added with 0.02, 0.04, 0.06, 0.08, 0.10, 0.12 and 0.14% of 10% H2O2 along with control one. All milk samples were kept at room temperature (28-310C). Flavor, clot on boiling (COB), acidity %, and methylene blue reduction (MBR) test were observed every one hour interval.Results: The milk samples were acceptable in terms of flavor up to 18 h at 0.14% H2O2. Similarly, this milk sample took maximum time (19 h) to give COB positive test. Acidity % was within normal range for 0.02, 0.04, 0.06, 0.08, 0.10, 0.12 and 0.14% H2O2 treated milk samples up to 8, 9, 11, 12, 12, 14, 17 and 18 h, respectively. Significant difference (P